PERAN BUDAYA KAIZEN, GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. NIKOMAS GEMILANG DI KOTA SERANG - Mahmudah, Mahmudah; Suparmoko, Muhammad; Maliki, Budi Ilham (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Productivity has an important role because a country's ability to produce goods and services determines the country's standard of living. The higher the level of productivity of a country, the greater the profits it will get, and vice versa. The purpose of this research is to determine and analyze the influence of kaizen culture, leadership style, and job satisfaction on work productivity. The approach and method used in this research is a quantitative approach with causal methods. Data collection techniques through questionnaires. The sampling method uses the Slovin formula, the sample is 95 respondents at PT. Nikomas Gemilang in Serang City.The results of the hypothesis test show that in the partial significance test each of the variables of kaizen culture and leadership style on productivity has a significance value greater than 0.05, job satisfaction on work productivity has a significance value smaller than 0.05. In a simultaneous test (F test) the variables of kaizen culture, leadership style and job satisfaction on productivity have a significance value of less than 0.05. The conclusion shows that the partial significance test of each of the kaizen culture variables and leadership style has no effect on work productivity, job satisfaction has an effect on work productivity. In a simultaneous test (F test) the variables of kaizen culture, leadership style and job satisfaction influence productivity.